Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae) - Zhang, Dong; Zhang, Ming; Wang, Chao; Pape, Thomas (Zootaxa, 2016)
An updated taxonomic catalog of all 32 species of the subfamily Paramacronychiinae so far known to occur in China is presented. The catalog includes data on type locality, references, distribution and information on type material for nominal species with a Chinese type locality. Additional specimens deposited in the Institute of Zoology, Chinese Academy of Sciences and the Museum of Beijing Forestry University were examined. The genus Wohlfahrtiodes Villeneuve, 1910 and the species Wohlfahrtiodes marzinowskyi Rohdendorf, 1962 are new records from China. Two new synonyms are proposed: Wohlfahrtia Brauer & Bergenstamm, 1889 = Sinotibetomyia Xue in Xue & Fei, 2011, syn. nov., and Wohlfahrtia atra Aldrich, 1926 = Sinotibetomyia curvifemura Xue & Fei, 2011, syn. nov.